2021
DOI: 10.1101/2021.06.23.21259247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific survival bias and interaction modeling in coronary artery disease risk prediction

Abstract: Background The 10-year Atherosclerotic Cardiovascular Disease (ASCVD) risk score is the standard approach to predict risk of incident cardiovascular events and recently, addition of CAD polygenic scores (PGSCAD) have been evaluated. Although age and sex strongly predict the risk of CAD, their interaction with genetic risk prediction has not been systematically examined. Objectives This study performed an in-depth evaluation of age and sex effects in genetic CAD risk prediction. Methods The population-based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…PRS-guided, lipid-lowering treatment, particularly for those at intermediate risk, has shown promise in decreasing cardiovascular disease events 2,39,40 . With a safe, effective and inexpensive preventative therapeutic, screening strategies for cardiovascular disease that consider PRS and conventional risk factors jointly (for example in a primary care population of at least 40 years of age 39 ) or that take a 2-stage approach (screening first with PRS then with conventional risk factors, or vice versa 40,41 ) appear to robustly provide clinical benefit; however, further refinement regarding whom and when to treat is still necessary.…”
Section: Slowing Disease Progression and Recurrencementioning
confidence: 99%
“…PRS-guided, lipid-lowering treatment, particularly for those at intermediate risk, has shown promise in decreasing cardiovascular disease events 2,39,40 . With a safe, effective and inexpensive preventative therapeutic, screening strategies for cardiovascular disease that consider PRS and conventional risk factors jointly (for example in a primary care population of at least 40 years of age 39 ) or that take a 2-stage approach (screening first with PRS then with conventional risk factors, or vice versa 40,41 ) appear to robustly provide clinical benefit; however, further refinement regarding whom and when to treat is still necessary.…”
Section: Slowing Disease Progression and Recurrencementioning
confidence: 99%
“…Time-stamped data allow studies of disease development and progression, such as risk prediction of coronary artery disease. 12 Some selected disease endpoints are presented in Table 2.…”
Section: Phenotypesmentioning
confidence: 99%
“…To overcome these limitations, we contribute to genetic studies worldwide through participation in consortia focused on a variety of diseases including cardiovascular disease, 43,44 lipids, 45,46 type 2 diabetes, 47 osteoporosis, 48 decline in kidney function, 49 Alzheimer's disease, 50 bipolar disease, 51 intracranial aneurysms, 52 insomnia, 53 respiratory health, 54 and sleepiness. 55 We also contributed HUNT data to studies of anthropometric traits, 56 alcohol and nicotine use, 57,58 COVID-19, 59 phenomewide discovery, 60 and genetic risk prediction, 12 among others. These contributions highlight efforts from researchers in equal parts from the K.G.…”
Section: Causal Inference and Family Effectsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 22, 2022. ; https://doi.org/10.1101/2022.07. 19.22277830 doi: medRxiv preprint Supplementary Table 1. Significantly higher AUC was continuously found in the PRS+ClinRS model even at ten years prior to disease diagnosis with an AUC of 0.79 (95% CI: 0.77-0.82), compared to baseline model (AUC: 0.72 [0.69-0.75]).…”
Section: Integrating Prs and Clinrs Enhances Heart Failure Predictionmentioning
confidence: 99%
“…Multiple studies have shown that using a PRSa weighted sum of genetic effects on certain diseases or traits across the human genomecan enhance disease prediction and further improve early prevention 6,18 . Multiple efforts have been made to summarize genetic and clinical information to identify high risk patients, but integrating high-dimensional genome-wide association study (GWAS) and electronic health record (EHR) in heart failure prediction models has not been previously evaluated [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%